Reassortment between seasonal and swine-origin H1N1 influenza viruses generates viruses with enhanced growth capability in cell culture - Octaviani, Cássio Pontes (2010)
One year after the emergence of the 2009 influenza (H1N1) pandemic, most cases have been relatively mild; however, the possibility of enhanced viral growth ability by reassortment with seasonal viruses cannot be overlooked. Here, we show that reassortant viruses containing a seasonal H1 HA and swine-origin NA and M genes have enhanced virus growth over their wild-type parental viruses. The emergence of such viruses in nature could, therefore, represent a threat.